Immune thrombocytopenic purpura and legionella infection: A case report highlighting the association. (2022) - Javed, Aneeqa; Alvi, Muhammad Junaid; Sahra, Syeda; DeChavez, Vincent
Abstract: Immune thrombocytopenic purpura (ITP) can be acquired or secondary to other drugs, infections, or autoimmune disorders. Legionella is a known intracellular organism that causes Legionnaire's disease and affects the lungs. Presented is the first case showing a direct association between Legionella and ITP. Our patient was a 61-year-old female with a past medical history of asthma whose clinical presentation was consistent with pneumonia secondary to Legionella . Her hospital course was complicated by critical bleeding with severe thrombocytopenia. She responded to antibiotics, steroids, and intravenous immunoglobulins (IVIG). Our case suggests an association between ITP and Legionella and emphasizes its timely diagnosis for appropriate treatment.